2005
DOI: 10.1128/jvi.79.16.10478-10486.2005
|View full text |Cite
|
Sign up to set email alerts
|

An Exonic Splicing Silencer Downstream of the 3′ Splice Site A2 Is Required for Efficient Human Immunodeficiency Virus Type 1 Replication

Abstract: Alternative splicing of the human immunodeficiency virus type 1 (HIV-1) genomic mRNA produces more than 40 unique viral mRNA species, of which more than half remain incompletely spliced within an HIV-1-infected cell. Regulation of splicing at HIV-1 3 splice sites (3ss) requires suboptimal polypyrimidine tracts, and positive or negative regulation of splicing occurs through binding of cellular factors to cis-acting splicing regulatory elements. We have previously shown that splicing at HIV-1 3ss A2, which produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(118 citation statements)
references
References 40 publications
9
108
1
Order By: Relevance
“…In addition, we observed that the deletion in exon 3 increased splicing efficiency (Fig. 4B), probably due to deletion of previously described splicing inhibitory sequences (10,17). In contrast, the deletion in intron 3 reduced splicing efficiency (Fig.…”
Section: Inhibition Of the 5ј-splice Site Of Exon 3 By Srp55 And Srp7mentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, we observed that the deletion in exon 3 increased splicing efficiency (Fig. 4B), probably due to deletion of previously described splicing inhibitory sequences (10,17). In contrast, the deletion in intron 3 reduced splicing efficiency (Fig.…”
Section: Inhibition Of the 5ј-splice Site Of Exon 3 By Srp55 And Srp7mentioning
confidence: 58%
“…These authors speculate that ASF/SF2 enhances splicing to the 3Ј-splice site of exon 3, either through a yet unidentified splicing enhancer, or by inhibiting a previously identified splicing silencer in exon 3 named ESSV (10,17). This splicing silencer interacts with heterogeneous nuclear ribonucleoprotein A/B (10,17,41), and ASF/SF2 is known to counteract heterogeneous nuclear ribonucleoprotein A1, another member of the heterogeneous nuclear ribonucleoprotein family (42,43). However, ASF/SF2 binds to the GAR enhancer and is necessary for (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A) (13,23,24). Mutations of 5Јss D2 that increase its binding affinity for U1 snRNP result in increased splicing at 3Јss A1 and increased vif mRNA, whereas mutations which lower the affinity to U1 snRNP result in decreased splicing at 3Јss A1 and reduced vif mRNA (13,25).…”
mentioning
confidence: 99%
“…Thus, the introns are inefficiently removed by the splicing machinery, which in turn, results in the accumulation of mRNAs with retained introns. Various other positive and negative cis-acting elements within the viral genome can also regulate the levels of intron-retaining viral mRNAs in the nucleus by regulating splicing (146).…”
Section: Nuclear Export Of Viral Mrnas and The Rev-rre Pathwaymentioning
confidence: 99%